USING THE SLEUTH MODEL TO SIMULATE FUTURE URBAN GROWTH IN THE GREATER EASTERN ATTICA AREA, GREECE - Stylianos Mathioulakis; Yorgos N. Photis (European Journal of Geography)
Urban sprawl is, undoubtedly, a global phenomenon that has been in effect since the dawn of civilization and has been an intriguing subject, primarily in the research field of geography. In recent years, the need to forecast and simulate real-world urban processes has led to advancements in computational methods on modeling these patterns. This paper reviews how primitive forms of urban settlements have gradually shaped into today’s contemporary cities. In addition, the causes, types and impacts of urban sprawl are examined given the importance to predict negative effects when an urban project is built. Lastly, this study includes an application of a Cellular Automaton (CA) Urban Growth Model (UGM) in order to simulate future urban growth. For this endeavor, the greater area of Eastern Attica, Greece was chosen as case study due to the fact that it yet has vast non-urban areas that could be converted to urban in the foreseeable future. To produce the final simulation output, various sources of digital imagery were used and then processed according to the model’s specific format. The final prediction scenario presents urban growth for the year of 2045 on Eastern Attica.